2014
DOI: 10.1111/boj.12194
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite evidence for low genetic diversity and reproductive isolation in tetraploidCentaurea seridis(Asteraceae) coexisting with diploidCentaurea asperaand triploid hybrids in contact zones

Abstract: Survival of polyploids in nature depends on several factors, including competition from diploid relatives and increased genetic diversity. Unlike other reported Centaurea polyploid complexes, diploid Centaurea aspera and tetraploid Centaurea seridis coexist in hybrid zones with frequent triploid individuals. The polyploid origin of C. seridis, the genetic diversity and population structure of the three cytotypes, and the degree of genetic differentiation among them were analyzed in seven mixed-ploidy zones, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 75 publications
3
38
0
Order By: Relevance
“…Most studies on polyploid complexes have revealed higher genetic diversity in polyploids than in diploids (e.g. Eliášová et al 2013 and references therein; but see Ferriol et al 2014). However, we explicitly investigated this difference with a focus on GCTs.…”
Section: Consequences Of Polyploid Formation For Genetic Diversitymentioning
confidence: 99%
“…Most studies on polyploid complexes have revealed higher genetic diversity in polyploids than in diploids (e.g. Eliášová et al 2013 and references therein; but see Ferriol et al 2014). However, we explicitly investigated this difference with a focus on GCTs.…”
Section: Consequences Of Polyploid Formation For Genetic Diversitymentioning
confidence: 99%
“…subdecurrens Mateo & Crespo, have been cited. These have been found between northern Castell on and Almer ıa on coastal sand dunes (El Saler, Santa Pola, Guardamar and Calblanque) and on coastal pebble dunes (Marjal dels Moros and Chilches) Ferriol et al 2012Ferriol et al , 2014. In Sax (inland Alicante), C. aspera subsp.…”
Section: Study Species and Study Areamentioning
confidence: 91%
“…cruenta also coexist, and hybrid individuals C. x subdecurrens nothosubsp. oblanceolata Merle et al have been observed Ferriol et al 2014).…”
Section: Study Species and Study Areamentioning
confidence: 96%
See 2 more Smart Citations